Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai pada Dinas Lingkungan Hidup Provinsi DKI Jakarta - Syafitriyani Syafitriyani; Natal Indra (Master Manajemen, 2024)
Employee performance is very important for the success of an agency because it determines whether the agency will succeed in achieving its goals or not. This study uses a quantitative approach to investigate the effect of workload and work environment on employee performance at the DKI Jakarta Provincial Environmental Agency. Data was collected through questionnaires, with 70 employees of the DKI Jakarta Provincial Environmental Agency as respondents. Using SPSS 24, the results of the analysis show that by 66.5%, workload and work environment have a simultaneous influence on employee performance and the rest is influenced by other factors not examined in this study.